Критерии выбора микроконтроллера - Адамович, В. Р. (ХНУРЕ, 2019)
In this work were examined the basic families of modern microcontrollers, such as 8051-compatible microcontrollers, STM32. Some aspects of their history, architecture and physical characteristic. Also were inspected their fundamental differences, distinctive features and scope between each other.